HUBUNGAN KONFORMITAS TEMAN SEBAYA DENGAN PERILAKU BULLYING PADA PESERTA DIDIK KELAS XI - Cyndia Meltani; Linda Fitria; Rini Sefriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the relationship between peer conformity and bullying behavior among Grade XI students at SMK Semen Padang in the 2024/2025 academic year. The research used a quantitative correlational method. The population consisted of 93 Grade XI students enrolled in the 2024/2025 academic year, with the entire population taken as the sample using a total sampling technique. The study investigated the correlation between peer conformity and bullying behavior. The instrument used to collect data was a Likert-scale questionnaire. Data analysis was conducted using the SPSS 21 statistical software and Microsoft Excel. Based on the data analysis, the hypothesis test results showed that the calculated r value was 0.401, while the r table value was 0,204. Since the calculated r is greater than the table value (0.401 >0,204), the hypothesis is accepted, indicating a positive relationship between peer conformity and bullying behavior among Grade XI students at SMK Semen Padang. Therefore, bullying behavior can be reduced if students experience healthy peer conformity and are in a supportive environment.